From Principle to Practice: Constitutional Principles and the Transformation of Party Finance in Germany and Italy - PELIZZO, Riccardo (Institutional Knowledge at Singapore Management University, 2004)
The paper investigates the development of party finance and party finance legislation in Germany and Italy. The main claim of the paper is that the differences between German and Italian party finance reflect differences in the party finance legislation enacted in the two countries, which, in their turn, are a result of how the German and the Italian constitutional principles were translated into practice.